Glyphosate induced nucleic acid alterations in freshwater fish, Catla catla - Naga, Prasanna; K, VEERAIAH; PADMAJA, PADMAJA; RAM, SAI; CH, VIVEK (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The freshwater fish, Catla catla were exposed to lethal and sub-lethal concentrations of glyphosate (glycil SL 41%) to study the alterations in the nucleic acid (DNA and RNA) content of various tissues (gill, brain, liver, kidney and muscle) after exposure to 24, 48, 72 and 96 h LC50. In static method the LC50 values were found to be 6.622, 6.546, 6.05 and 5.798 mg/L respectively for 24, 48, 72 and 96 h and in continuous flow-through system the LC50 values were 5.759, 5.374, 5.249 and 5.191 mg/L respectively for 24, 48, 72 and 96 h. In both the methods the LC50 values showed decreased trend with time of exposure and the decrease is more in continuous flow through method than in static method. A decline in the DNA and RNA content was observed and the percentage decrease is more apparent at lethal concentrations than at sub-lethal concentrations.